Current State of Microsurgical Treatment of Aneurysms of the Ophthalmic Segment of the Internal Carotid Artery - I. N. Sever; D. V. Litvinenko; V. V. Tkachev (Инновационная медицина Кубани)
There is a clear trend towards an increase in the number of endovascular interventions for cerebral aneurysms; however, open surgery remains the method of choice for some patients with ruptured and complex aneurysms. For example, the best treatment method for aneurysms of the ophthalmic segment of the internal carotid artery (ICA) is still up to debate. A large number of publications on surgical treatment of carotid-ophthalmic aneurysms do not give clear guidelines in which cases microsurgical or endovascular techniques should be used. There are no Russian papers comparing the results of open and endovascular surgery depending on the clinical course of the disease. We analyze problems of microsurgical treatment of carotid-ophthalmic aneurysms and present data on epidemiology, variations in clinical course, topographic and anatomical features of aneurysms of the ophthalmic segment. The article discusses possibilities of modern diagnostic radiology, the choice of surgical approach, the technique of aneurysm dissection, and methods of proximal control of intraoperative bleeding. Numerous classifications of aneurysms of the ophthalmic segment of the ICA were systematized.